Disorders of Consciousness: Ethical Issues of Diagnosis, Treatment, and Prognostication - Septien, Spencer; Rubin, Michael A. (Seminars in Neurology, 2018)
Consciousness defines our humanity more than any other biologic phenomena that a clinician might be called upon to examine, diagnose, or treat. When family comes to the bedside of a patient, they hope to find them talking, thinking, and feeling. The complexity of consciousness allows an expansive gradation of dysfunction such that we must consider numerous potential insults, possible interventions, and often an unknown likelihood of recovery. As value-laden questions are more often in the hands of surrogate decision makers, the neurologist is given the herculean task of not only diagnosing and treating alterations of consciousness but also predicting the likely course of the disease to empower surrogates to make a choice most consistent with the preferences of the patient. The degree of uncertainty in the diagnosis and prognosis demands that the clinician consider the ethics of the diagnosis, treatment, and prognostication of disorders of consciousness. Expectations of acute and chronic care, the extent of the formal neurological investigation, the potential of therapeutic trials, the self-fulfilling prophecy that can occur with prognostication, and the challenges of shared decision making are all subjects that we explore.
Keywords: ethics; prognostication; devastating brain injury; disorders of consciousness; coma; vegetative state